Teaching types with a cognitively effective worked example format. (17th December 2015) - TIRRONEN, VILLE; ISOMÖTTÖNEN, VILLE
Abstract: Teaching functional programming as a second programming paradigm is often difficult as students can have strong preconceptions about programming. When most of these preconceived ideas fail to be confirmed, functional programming may be seen as an unnecessarily difficult topic. A typical topic that causes such difficulties is the language of types employed by many modern functional languages. In this paper, we focus on addressing this difficulty through the use of step-by-step calculations of type expressions. The outcome of the study is an elaboration of a worked example format and a methodical approach for teaching types to beginner functional programmers.